ANALYSIS OF SONG STRUCTURE A SING SING SO ARRANGEMENT OF BIAN LIUNIAN - Ruth Vicky Sianturi; Herna Hirza (Universitas Negeri Medan, 2019)
The research aims to determine the structure and arrangement of the song A Sing sing So arrangement Bian Liunian. The theories used in this study include the understanding of analysis, the understanding of structures, the notion of music, the understanding of interpretation, the understanding of songs, the definition of A Sing Sing So. This research uses a qualitative method of descriptive research that is a research method aimed to describe in detail and clearly about a phenomenon that is the focus of research. This study is a qualitative descriptive study, therefore, this research was conducted in the laboratory of Sendratasik department which was carried out in February 2019 – June 2019. The results of this study show that the song of A Sing Sing So of Bian Liunian arranger has 13 motifs along with its supporting motif, has 6 phrases consisting of phrase questions and answers, this song is also a two-part song consisting of part A and B. Arrangement of this song can be seen from the melody, rhythm and harmonization of Mandarin nuance but the interpretation of the song does not correspond to the meaning of the actual song.